: Aktualisasi Nilai-Nilai Perkembangan Anak Pada Film “Adit dan Sopo Jarwo” - Sri W Yuni; Ida Yeni Rahmawati; Nurtina Irsyad Rusdiani (Jurnal Kajian Anak (J-Sanak), 2024)
Animated films play a big role in education, this can be seen from the moral messages and behavior conveyed by animators to children to do good things, for example the animated cartoon films Adit and Sopo Jarwo. The aim of this research is to determine the actualization of child development values ​​in the films Adit and Sopo Jarwo. The research used is a descriptive qualitative method. The actualization of children's development values ​​can be seen in showing this film to children. A fairly well-known animation that children know is the animated cartoon film Adit Sopo Jarwo. Based on the results and discussion of descriptive qualitative research methods from primary and secondary data on 3 episodes of the animated film Adit and Sopo Jarwo, 4 aspects were obtained, namely religious values, physical motoric values, social emotional values ​​and artistic values.